Municipal solid waste landfill site selection with geographic information systems and analytical hierarchy process: a case study in Mahshahr County, Iran. Issue 1 (January 2013) - Alavi, Nadali; Goudarzi, Gholamreza; Babaei, Ali Akbar; Jaafarzadeh, Nemat; Hosseinzadeh, Mohsen
Landfill siting is a complicated process because it must combine social, environmental and technical factors. In this study, in order to consider all factors and rating criteria, a combination of geographic information systems and analytical hierarchy process (AHP) was used to determine the best sites for disposal of municipal solid waste (MSW) in Mahshahr County, Iran. In order to the decision making for landfill siting a structural hierarchy formed and the most important criteria: surface water, sensitive ecosystems, land cover, urban and rural areas, land uses, distance to roads, slope and land type were chosen according to standards and regulations. Each criterion was evaluated by rating methods. In the next step the relative importance of criteria to each other was determined by AHP. Land suitability for landfill was evaluated by simple additive weighting method. According to the landfill suitability map, the study area classified to four categories: high, moderate, low and very low suitability areas, which represented 18.6%, 20.3%, 1.6 and 0.8% of the study area respectively. The other 58.7% of the study area was determined to be completely unsuitable for landfill. By considering the parameters, such as the required area for landfill, distance to MSW generation points, and political and management issues, and consulting with municipalities managers in the study area, six sites were chosen for site visiting. The result of field study showed that it is a supplementary, and necessary, step in finding the best candidate landfill site from land with high suitability.